Analisis Kesiapan Sumber Daya Dalam Mitigasi Kebakaran Pos Pemadam Kebakaran Tropodo Sidoarjo - Ludjiansjah, Farah Auliya; Tribuana, Keista Romadhona; Syafira, Nazwa Aulia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
Densely populated residential and industrial areas like Tropodo have a high vulnerability to fire disasters due to narrow road access, thus demanding optimal operational readiness from the nearest fire station. This study aims to analyze the readiness of human resources, facilities and infrastructure, and operational strategies for fire mitigation at the Tropodo Fire Station, Sidoarjo. This descriptive qualitative research utilizes George C. Edwards III’s policy implementation theory, focusing strictly on the resource variable. Data were collected through in-depth interviews, direct observations, and documentation, with the Squad Commander and station personnel serving as the primary sample. The findings indicate that while the human resources are qualitatively competent and certified, there is a significant quantitative shortage with only five personnel available per standby shift. Facilities are generally adequate but constrained by budget limitations for updating Personal Protective Equipment (PPE) and the lack of tactical fleets to access densely populated areas with narrow alleys. Operational strategies implemented include 24-hour shifts, utilization of the 112 Call Center, and community education, although challenges like traffic congestion and prank calls persist. The study recommends that the local government increase the number of field personnel, allocate specific budgets for PPE renewal and compact fire trucks procurement, and optimize community education regarding independent fire protection. Keyword : Fire Mitigation, Resource Readiness, Fire Station